Widespread continental mtDNA lineages prevail in the bumblebee fauna of Iceland - Grigory S. Potapov; Alexander V. Kondakov; Yulia S. Kolosova; Alena A. Tomilova; Boris Yu. Filippov; Mikhail Yu. Gofarov; Ivan N. Bolotov (ZooKeys, 2018)
Origins of the fauna in Iceland is controversial, although the majority of modern research supports the postglacial colonization of this island by terrestrial invertebrates rather than their long-term survival in glacial refugia. In this study, we use three bumblebee species as a model to test the hypothesis regarding possible cryptic refugia in Iceland and to evaluate a putative origin of recently introduced taxa. Bombus jonellus is thought to be a possible native Icelandic lineage, whereas B. lucorum and B. hortorum were evidently introduced in the second half of the 20th century. These phylogeographic analyses reveal that the Icelandic Bombus jonellus shares two COI lineages, one of which also occurs in populations on the British Isles and in mainland Europe, but a second lineage (BJ-02) has not been recorded anywhere. These results indicate that this species may have colonized Iceland two times and that the lineage BJ-02 may reflect a more ancient Late Pleistocene or Early Holocene founder event (e.g., from the British Isles). The Icelandic populations of both Bombus lucorum and B. hortorum share the COI lineages that were recorded as widespread throughout Eurasia, from the European countries across Russia to China and Japan. The findings presented here highlight that the bumblebee fauna of Iceland comprises mainly widespread ubiquitous lineages that arrived via natural or human-mediated dispersal events from the British Isles or the mainland.